Moral judgement competence and moral attitudes of medical students - Slováčková, Birgita; Slováček, Ladislav (Nursing ethics, 2007)
A cross-sectional study explored the moral judgement competence and moral attitudes of 310 Czech and Slovak and 70 foreign national students at the Medical Faculty of Charles University in Hradec Králové, Czech Republic. Lind's Moral Judgement Test was used to evaluate moral judgement competence and moral attitudes depending on factors such as age, number of semesters of study, sex, nationality and religion. Moral judgement competence decreased significantly in the Czech and Slovak medical students as they grew older; in medical students from other countries it did not significantly increase. The influence of other factors (sex, nationality and religion) on moral judgement competence was not proven in either the Czech and Slovak or the foreign national medical students. Moral attitudes do not change; the Czech and Slovak as well as the foreign students preferred the post-conventional levels of moral judgement (Kohlberg's 5th and 6th stages). The fact that the Czech and Slovak students' moral judgement competence decreased with age and number of semesters of study completed is not an optimistic sign: medical students who had undergone a lower number of semesters of study were morally more competent.
Keywords: Regression Analysis; dospělí; odborná způsobilost; průzkumy a dotazníky; Female; zahraniční odborný personál; charakteristiky bydlení; Foreign Professional Personnel; Age Factors; multivariační analýza; postoj zdravotnického personálu; Adult; ženské pohlaví; průřezové studie; lékařská etika; Multivariate Analysis; Surveys and Questionnaires; Adolescent; Slovakia; věkové faktory; Nursing Methodology Research; lidé; Judgment; Students, Medical; regresní analýza; Attitude of Health Personnel; studenti lékařství; Residence Characteristics; Cross-Sectional Studies; Male; Czech Republic; Education, Medical, Undergraduate; Health Knowledge, Attitudes, Practice; zdraví - znalosti, postoje, praxe; mínění; mravy; Česká republika; Morals; Ethics, Medical; Slovenská republika; mužské pohlaví; studium lékařství pregraduální; Professional Competence; ošetřovatelská metodologie - výzkum; mladiství; Humans